P107 How significant is the lack of formulations for paediatric inpatients?. Issue 6 (17th May 2019) - Zahn, J; Rascher, W; Neubert, A
Abstract : Background: Pharmacotherapy in children is complex requiring individual dosages of an active substance which are often not compatible with commercially available medicinal products. 1–2 Manipulations of medicinal products, e.g. splitting or mortaring of tablets are common practice and often unavoidable although they entail risks for the patient as they can affect dosing accuracy, bioavailability and integrity of the dosage form. 3–4 In this study we aim to determine how many medicines have to be manipulated before administration in a hospital setting in Germany. Methods: A prospective observational approach was used to determine all manipulations of drugs orally administered on two wards of a German children´s hospital. A pharmacist systematically observed the nurses and documented all steps of the medication preparation processes for 7 days. Data was analysed using descriptive analysis. Types of manipulations were evaluated on the basis of the relevant summary of product characteristics (SmPC). Results: During the pilot phase 170 medication preparation processes were monitored. In 36, 5% (n=62) of the observed processes medicines had to be manipulated. 54, 3% (n=19) of the patients were affected by at least one manipulation. 48, 4% (n=30) of all manipulations were unauthorized by the relevant SmPC affecting 37, 1% of the patients. In 60, 0% the reason for unauthorized manipulation was unsuitable strength of the available formulation. Dosage forms affected by unauthorized manipulations were tablets (n=28) and granules (n=2). Active substances most frequently involved in unauthorized manipulations were Omeprazole (n=11), Phenobarbital (n=7) and Topiramat (n=3). Conclusion: Overall, these results reveal that manipulations to medicines prior to administration are frequent on paediatric wards in Germany. About half of the manipulations are unauthorized indicating that no suitable paediatric formulation is available. Further investigation is needed to determine the preventability and the risks associated with the overall aim of improving safety of drug therapy in children. References: Schirm E, Tobi H, de Vries TW, Choonara I, De Jong-van den Berg LT. Lack of appropriate formulations of medicines for children in the community. Acta paediatrica (Oslo, Norway: 1992) 2003;92(12):1486–9. Richey RH, Craig JV, Shah UU, Nunn AJ, Turner MA, Barker CE, et al. MODRIC - Manipulation of drugs in children. International journal of pharmaceutics . 2013;457(1):339–41. Bjerknes K, Boyum S, Kristensen S, Brustugun J, Wang S. Manipulating tablets and capsules given to hospitalised children in Norway is common practice. Acta paediatrica (Oslo, Norway: 1992) 2017;106(3):503–8. Paparella S. Identified safety risks with splitting and crushing oral medications. Journal of emergency nursing: JEN: of ficial publication of the Emergency Department Nurses Association 2010;36(2):156–8. Disclosure(s): Nothing to disclose